(untitled) (PUBMET, 2025)
Researchers’ open access publishing (OAP) attitudes and practices are shaped by a complex interplay of factors, including the characteristics of scientific disciplines and the overall settings in which authors and journals operate. They are influenced not only by the authors’ awareness of the benefits of open access and financial aspects of publishing, but also by various micro-characteristic like requirements for academic promotion, institutional or governmental mandates, OA advocacy, and incentives for publishing in OA.